Intensity attacks of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) on several corn varieties in Kediri, East Java, Indonesia - DIDIK SUDIHARDJO; SAMANHUDI SAMANHUDI; SHOLAHUDDIN SHOLAHUDDIN; BAMBANG PUJIASMANTO; MUJI RAHAYU; ANDRIYANA SETYAWATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sudihardjo D, Samanhudi, Sholahuddin, Pujiasmanto B, Rahayu M, Setyawati A. 2023. Intensity attacks of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) on several corn varieties in Kediri, East Java, Indonesia. Biodiversitas 24: 6979-6987. The presence of Spodoptera frugiperda J.E. Smith, 1797 attack on corn is one of the main causes of the decrease in yield. Local, composite, and hybrid corn have different characteristics and will affect intensity attack and foliar damage due to S. frugiperda attack. This study aimed to determine the intensity of the attack of several types of local corn, composites, and hybrids against S. frugiperda. The research was conducted in the Kediri region, East Java, one of the corn cultivation centers. The study used a completely randomized block design with three replications of 18 varieties of various local, composites, and hybrid corn varieties. Local corn varieties consist of Madura Putih, Kebo Bima, Manik Liu, Lameran-Latim, Seraye-Bali, Madura kuning, and Sumbawa. Composite corn varieties include Bisma, Puput Uri, Srikandi Ungu, and Sukmaraga. Furthermore, the hybrid varieties comprise ADV Jago, Bisi 18, DK 77, NK 6172, P 27, Pertiwi 3, and R7. The results showed the infestation of S. frugiperda in all corn varieties peaked at age 42 DAP, with the intensity attack reaching 100%. The lowest intensity attack rate of S. frugiperda was obtained by the Sukmaraga composite variety and the NK6172 hybrid variety tends to be more resistant to S. frugiperda attacks than composite and local varieties. All corn-tested varieties were attached by S. frugiperda, which varied for the percentage of plant damage, severity level, and the time the pest attack first attacked. The clustering groups of each corn variety were based on the intensity attack of S. frugiperda, number of larvae, severity level and early infestation founded group resistant, which have less foliar damage due to S. frugiperda larvae attacks consisting of 5 varieties: Madura kuning, Madura Putih, Bisma, NK6172, and Srikandi Ungu.